The risk of congenital malformations, perinatal mortality and neonatal hospitalisation among pregnant women with asthma: a systematic review and meta‐analysis. Issue 7 (26th March 2013) - Murphy, VE; Wang, G; Namazy, JA; Powell, H; Gibson, PG; Chambers, C; Schatz, M
<x xml:space="preserve">Abstract</x> Background There is conflicting literature on the effect of maternal asthma on congenital malformations and neonatal outcomes. Objectives This review and meta‐analysis sought to determine if maternal asthma is associated with an increased risk of adverse neonatal outcomes. Search strategy We searched electronic databases for: (asthma or wheeze) and (pregnan* or perinat* or obstet*). Selection criteria Cohort studies published between 1975 and March 2012 reporting at least one perinatal outcome of interest (congenital malformations, neonatal complications, perinatal mortality). Data collection and analysis In all, 21 studies met inclusion criteria in pregnant women with and without asthma. Further analysis was conducted on 16 studies where asthmatic women were stratified by exacerbation history, corticosteroid use, bronchodilator use or asthma severity. Main results Maternal asthma was associated with a significantly increased risk of congenital malformations (relative risk [RR] 1.11, 95% confidence interval [95% CI] 1.02–1.21, I2 = 59.5%), cleft lip with or without cleft palate (RR 1.30, 95% CI 1.01–1.68, I2 = 65.6%), neonatal death (RR 1.49, 95% CI 1.11–2.00, I2 = 0%), and neonatal hospitalisation (RR 1.50, 95% CI 1.03–2.20, I2 = 64.5%). There was no significant effect of asthma on major malformations (RR 1.31, 95% CI 0.57–3.02, I2 = 70.9%) or stillbirth (RR 1.06, 95% CI 0.9–1.25, I2 = 35%). Exacerbations and use of bronchodilators and inhaled corticosteroids were not associated with congenital malformation risk. Authors' conclusions Despite limitations related to the observational nature of the primary studies, this review demonstrates a small increased risk of neonatal complications among pregnant women with asthma. Further investigations into mechanisms and potential preventive interventions to improve infant outcomes are required.